2017
DOI: 10.1038/s41467-017-01903-8
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin remodeling factor ISW-1 integrates organismal responses against nuclear and mitochondrial stress

Abstract: Age-associated changes in chromatin structure have a major impact on organismal longevity. Despite being a central part of the ageing process, the organismal responses to the changes in chromatin organization remain unclear. Here we show that moderate disturbance of histone balance during C. elegans development alters histone levels and triggers a stress response associated with increased expression of cytosolic small heat-shock proteins. This stress response is dependent on the transcription factor, HSF-1, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 47 publications
(64 reference statements)
0
42
0
Order By: Relevance
“…This study unravels an unexpected role of HSB-1/HSF-1 signaling in regulating levels of the core histone protein H4 and its previously unfound functions in modulating the transcription of mitochondrial genome-encoded genes. A recent study has shown that a mild disruption of mitochondrial activity in worms induces an imbalance in the levels of core histone proteins ( 5 ). This leads to elevated protein levels of some, but not all, core histones, increased transcription of HSF-1 target genes, and extension of life span that is dependent on a chromatin remodeling protein, ISW-1 ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study unravels an unexpected role of HSB-1/HSF-1 signaling in regulating levels of the core histone protein H4 and its previously unfound functions in modulating the transcription of mitochondrial genome-encoded genes. A recent study has shown that a mild disruption of mitochondrial activity in worms induces an imbalance in the levels of core histone proteins ( 5 ). This leads to elevated protein levels of some, but not all, core histones, increased transcription of HSF-1 target genes, and extension of life span that is dependent on a chromatin remodeling protein, ISW-1 ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that a mild disruption of mitochondrial activity in worms induces an imbalance in the levels of core histone proteins ( 5 ). This leads to elevated protein levels of some, but not all, core histones, increased transcription of HSF-1 target genes, and extension of life span that is dependent on a chromatin remodeling protein, ISW-1 ( 5 ). In agreement with these findings, our data also support the requirement of histone H4 in mediating the longevity-promoting effects of impaired mitochondrial function (fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This very last is associated to the Base Excision Repair (BER) and the Nucleotide Excision Repair (NER) mechanisms to help repair DNA after an oxidative insult [264]. Chromatin remodeling by its remodeler family SWI/SNF contributes to the response against stress and senescence, at the same time mitochondrial dysfunction induces chromatin remodeling responses [265]. The thioredoxing-interacting protein (TXNIP) is a protein known to have an important impact over OS, inflammation and apoptosis in the pancreas and the retina [266], in recent years it has been considered that these modifications lead to chromatin remodeling in retinal cells.…”
Section: Chromatin Remodelingmentioning
confidence: 99%
“…H2B cytoplasmic accumulation was detected using two different (monoclonal vs. polyclonal) anti-H2B antibodies. Both commercially available antibodies are extensively used to visualize H2B with high specificity and sensitivity [28][29][30]. Nonspecific binding of the secondary antibody was ruled out by incubating the cells with the secondary antibody only (see Fig 2).…”
Section: Plos Onementioning
confidence: 99%